Comparative effects of two in situ hybridization methods for the pinewood nematode (Bursaphelenchus xylophilus) - Wang, Chunyu; Zhuge, Junhao; Tang, Siqi; Zhou, Xiang; Zhou, Lifeng; Guo, Kai (Frontiers in Microbiology, 2023)
The gene localization technique of Bursaphelenchus xylophilus (pinewood nematode, PWN) is used for study gene expression in PWNs. Two in situ hybridization methods, namely, whole-mount in situ hybridization and the cut-off method are used widely. To compare the effects of these two in situ hybridization methods, the present study investigated the patterns of two functional genes expression in PWNs. The Bx-vap-2 gene (GenBank accession number: OR228482), related to pathogenicity, and the fem-2 gene (GenBank accession number: OR228481), related to sex determination, were selected to map related genes in the whole-mount and amputated PWNs at different ages using these in situ hybridization methods.Based on the overall statistical comparison, we found that compared to the cut-off method, the whole-mount method exhibited higher staining rates and correct staining rates for the fem-2 gene and Bx-vap-2 gene. However, considering the correct staining aspect, the cut-off method yielded better staining effects on pinewood nematode sections than the whole-mount method, with clearer hybridization signal locations and less non-specific staining. In other words, the cut-off method demonstrated more precise gene localization. Both methods are applicable for gene localization, but considering the overall staining pattern, analysis of experimental results, and comprehensive experimental operations, we believe that the whole-mount method is more suitable for gene localization and expression analysis of development-related genes in pinewood nematodes. This is because intact pinewood nematodes are better suited for showcasing the continuous developmental process of development-related genes. On the other hand, considering the experimental time, accuracy of staining site, and the amount of non-specific staining, the cut-off method is more suitable for disease-related genes. Additionally, to achieve better performance, the cut-off method can be Comparative effects of Two ISH Methods for PWN 2 selectively applied to samples during the experimental process.